Penilaian dan Evaluasi Kelayakan Dasar pada Rumah Potong Hewan Ruminansia Saat Meugang di Aceh Barat - Pakpahan, Novriaman; anggriawin, Mirza (JURNAL KAJIAN VETERINER, 2022)
Meugang is a tradition of consuming meat as a form of joy for the people of Aceh in welcoming the month of Ramadan or Eid. The quality and safety of meat is determined by the implementation of good methods of processing meat products in Slaughterhouse. The government has set standard rules that need to be carried out in the management of Slaughterhouse to produce safe, healthy, whole and halal fresh meat products through Regulation of the Minister of Agriculture of the Republic of Indonesia number II of 2020 concerning Certification of Veterinary Control Numbers of Animal Products Business Units. This study was intended to examine good manufacturing procedure in the animal product production chain in the Ruminant Slaughterhouse Business Unit (RPH-R) Aceh Barat district. The results showed that overall meat processing activities in RPH-R had a total of 22 major deviations and 23 minor deviations. This amount does not meet the Veterinary Control Number Level for the RPH-R Business Unit. The number of deviations is very large and the presence of microbial contamination in the meat samples is very worrying, so the relevant parties are advised to improve the implementation of animal slaughtering activities at the RPH-R Aceh Barat in accordance with the standard regulations that have been set.